Studi Audit Energi pada Gedung Sekolah untuk Optimalisasi Penggunaan Energi - Aulia Rahmah; Nuran, Andi Shridivia; Nurislamiah, Fathiyah (Micronic: Journal of Multidisciplinary Electrical and Electronics Engineering, 2025)
An energy audit at Madrasah Ibtidaiyah Negeri 1 Gowa was conducted to evaluate the efficiency of electricity consumption and identify potential energy savings in daily school operations. The methods included a preliminary energy audit involving annual energy consumption data collection and calculation of Energy Consumption Intensity (ECI), as well as a detailed audit of the lighting system. The results showed that the school building was categorized as efficient, with an initial ECI value of 0.701 kWh/m²/month. However, several rooms were found to have lighting levels below the standard, prompting the addition of energy-saving LED lamps. After these improvements, the ECI increased to 1.39 kWh/m²/month but remained within the efficient category. This audit demonstrates that improving lighting quality can be achieved without sacrificing overall energy efficiency and provides concrete recommendations for school energy management to support sustainable energy efficiency and environmental preservation